WORK ENVIRONMENT AS A MEDIATOR OF THE RELATIONSHIP BETWEEN JOB SATISFACTION AND JOB PERFORMANCE: A LITERATURE REVIEW - Nor Roselidyawaty Mohd Rokeman; Che Ghani Che Kob (Jurnal Penyelidikan Sains Sosial, 2023)
The work environment is a crucial catalyst for enhancing job satisfaction among vocational teachers in schools. Early retirement and career shifts among vocational teachers, driven by poor working conditions, can adversely impact both productivity and job performance. This study aims to comprehensively understand the dynamics of job satisfaction through a review of existing literature, thereby contributing to the discourse on previous findings. Specifically, it examines the role of the physical work environment in Malaysia as an intermediary factor that influences job performance in organizations. Employing empirical analysis of past studies, the paper explores the effects and relationships between job satisfaction, teacher performance, and achievement. It underscores the significance of job satisfaction in motivating teachers to nurture students who meet the industry requirements of the country. The study primarily focuses on the work environment as a mediating factor in job satisfaction and its contribution to performance achievement. The outcomes of this literature review are anticipated to enrich the empirical understanding of teacher job satisfaction in schools, offering valuable insights for policymakers, practitioners, and researchers in the field.